PERBEDAAN JUMLAH IKAT BIBIT TERHADAP PERTUMBUHAN RUMPUT LAUT (Kappaphycus alvarezii) MENGGUNAKAN METODE LONG LINE PANTAI AMAL KOTA TARAKAN - Cahyadi, Jimmy; Ihsan, Burhanuddin; Asrullah, Asrullah (Jurnal Borneo Saintek, 2023)
Seaweed is one of the fisheries commodities that is widely cultivated in Indonesia. The cultivation of seaweed (Kappaphycus alvarezii) in the Coastal Waters of Amal Baru, Tarakan City, is traditionally done using the longline method. The gillnet method is the most used method by seaweed farmers because it is flexible in choosing locations and relatively inexpensive. The research aims to determine the difference in the number of seaweed seedlings on the absolute and specific growth rates. This study used a Completely Randomized Design (CRD) with 4 treatments and 3 replications. Treatment P1 (1 bundle), P2 (2 bundles), P3 (3 bundles), and P4 (4 bundles). The results showed that the growth of seaweed seedlings with different numbers of bundles influenced absolute and specific growth rates. The best treatment was found in treatment P4 with an average absolute growth rate of 80.00% and an average specific growth rate of 100%.